Pain after major elective orthopedic surgery of the lower limb and type of anesthesia: does it matter? - Pereira,Diogo Luís (2016)
Abstract Background and objectives: Total knee arthroplasty and total hip arthroplasty are associated with chronic pain development. Of the studies focusing on perioperative factors for chronic pain, few have focused on the differences that might arise from the anesthesia type performed during surgery. Methods: This was a prospective observational study performed between July 2014 and March 2015 with patients undergoing unilateral elective total knee arthroplasty (TKA) or total hip arthroplasty (THA) for osteoarthritis. Data collection and pain evaluation questionnaires were performed in three different moments: preoperatively, 24 hours postoperatively and at 6 months after surgery. To characterize pain, Brief Pain Inventory (BPI) was used and SF-12v2 Health survey was used to further evaluate the sample's health status. Results: Forty and three patients were enrolled: 25.6% men and 74.4% women, 51,2% for total knee arthroplasty and48.8% for total hip arthroplasty, with a mean age of 68 years. Surgeries were performed in 25.6% of patients under general anesthesia, 55.8% under neuraxial anesthesia and 18.6% under combined anesthesia. Postoperatively, neuraxial anesthesia had a better pain control. Comparing pain evolution between anesthesia groups, neuraxial anesthesia was associated with a decrease in “worst”, “medium” and “now” pain at six months. Combined anesthesia was associated with a decrease of “medium” pain scores at six months. Of the three groups, only those in neuraxial group showed a decrease in level of pain interference in “walking ability”. TKA, “worst” pain preoperatively and general were predictors of pain development at six months. Conclusions: Patients with gonarthrosis and severe pain preoperatively may benefit from individualized pre- and intraoperative care, particularly preoperative analgesia and neuraxial anesthesia.